Utilization of Liquid Smoke for Odor Control at the Final Disposal Site Kalibaru, Banyuwangi - Rosyid Ridho; M. Sabiq Irwan H; Eko Malis; Mislan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
The implementation of community service with the theme of utilizing liquid smoke for odor control in garbage at the Kalibaru Final Disposal Site has been carried out. This service was carried out in three stages, namely counseling, visits to liquid smoke factories and application of liquid smoke to garbage. The results of these activities in general, the community really understands and is able to carry out the processing of waste with liquid smoke independently, but the motivation for entrepreneurship from liquid smoke products has increased at the time of counseling, only 23.3 percent of participants were interested in entrepreneurship, but during a visit at liquid smoke factory even at the time of application all participants were interested in entrepreneurship because of the ease of process and high benefits. Key words: Liquid Smoke, Garbage, Kalibaru